P38β (MAPK11) mediates gemcitabine-associated radiosensitivity in sarcoma experimental models. (March 2021) - Pascual-Serra, R.; Fernández-Aroca, D.M.; Sabater, S.; Roche, O.; Andrés, I.; Ortega-Muelas, M.; Arconada-Luque, E.; Garcia-Flores, Natalia; Bossi, G.; Belandia, B.; Ruiz-Hidalgo, M.J.; Sánchez-Prieto, R.
Highlights: The p38MAPK signalling pathway mediates the radiosensitizing effect of gemcitabine. Although abrogation of p38α promotes resistance to gemcitabine, this MAPK is not implicated in the radiosensitizing potential of this drug in sarcoma-derived cell lines. p38β is the MAPK that mediates the radiosensitivity associated to gemcitabine in sarcoma-derived cell lines. p38β should be analyzed in those cases in which gemcitabine is combined with ionizing radiation in order to select the most adequate patients for this combination. Abstract: Background and purpose: Gemcitabine is an antitumour agent currently used in the treatment of several types of cancer with known properties as a radiosensitizer. p38MAPK signalling pathway has been shown to be a major determinant in the cellular response to gemcitabine in different experimental models. However, the molecular mechanism implicated in gemcitabine-associated radiosensitivity remains unknown. Materials and methods: The human sarcoma cell lines A673 and HT1080, and a mouse cell line derived from a 3-methylcholanthrene induced sarcoma were used as experimental models. Modulation of p38MAPKs was performed by pharmacological approaches (SB203580) and genetic interference using lentiviral vectors coding for specific shRNAs. Viability was assessed by MTT. Gene expression was evaluated by western blot and RT-qPCR. Induction of apoptosis was monitored by caspase 3/7 activity. Response to ionizing radiation was evaluated by clonogenic assays. Results: Our data demonstrate that chemical inhibition of p38MAPK signalling pathway blocks gemcitabine radiosensitizing potential. Genetic interference of MAPK14 (p38α), the most abundantly expressed and best characterized p38MAPK, despite promoting resistance to gemcitabine, it does not affect its radiosensitizing potential. Interestingly, specific knockdown of MAPK11 (p38β) induces a total loss of the radiosensitivity associated to gemcitabine, as well as a marked increase in the resistance to the drug. Conclusion: The present work identifies p38β as a major determinant of the radiosensitizing potential of gemcitabine without implication of p38α, suggesting that p38β status should be analysed in those cases in which gemcitabine is combined with ionizing radiation.